Biomimetic catechol-based adhesive polymers for dispersion of polytetrafluoroethylene (PTFE) nanoparticles in an aqueous medium. Issue 7 (23rd January 2020) - Grewal, Manjit Singh; Yabu, Hiroshi
Abstract : Biomimetic synthetic functional materials are valuable for a large number of practical applications with improved or tunable performance. Abstract : Biomimetic synthetic functional materials are valuable for a large number of practical applications with improved or tunable performance. In this paper, we present a series of mussel-inspired biomimetic catechol-containing copolymers synthesized from dopamine methacrylamide (DMA) and 2-(2-ethoxyethoxy)ethyl acrylate (EEA) and abbreviated as poly(PDMA-PEEA). The successfully synthesized adhesive polymers allow adhering polytetrafluoroethylene (PTFE) and were used for coating PTFE particles in organic solvent and re-dispersion in an aqueous medium. Adhesive polymer coated PTFE particles were efficiently used as a nanoreactor for generating silver (Ag) metal nanoparticles (NPs).